Interpretation Of The Four Symbols In Yusuf Khos Hajib’s Work “Kutadgu Bilig” - Husaynova, Manzurahon Olimovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
The work expresses the idea of ​​a perfect society and a perfect person through the images of four main symbols - Kuntugdi (justice), Aitoldi (happiness), Ogdulmish (reason) and Ozgurmish (satisfaction). Each symbol represents a certain social and moral value, and it is emphasized that their mutual harmony is the basis of state stability and human perfection. The author philosophically reveals the importance of fair governance, intelligence, spiritual purity and prosperity through these symbolic characters.